2019
DOI: 10.1590/1980-57642018dn13-030012
|View full text |Cite
|
Sign up to set email alerts
|

Subjective memory complaint and its relationship with cognitive changes and physical vulnerability of community-dwelling older adults

Abstract: Memory complaint (MC) is common in older adults and can be confirmed by people close to them, such as family members and caregivers. Studies show an association between MC and cognitive impairment and, hence, physical vulnerability may exacerbate MC. However, the relationship between MC and physical vulnerability is not yet clear in the literature.\ Objective: to investigate the association between MC, cognitive impairment, and physical vulnerability. Methods: this is a cross-sectional study. We evaluated 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 39 publications
0
8
0
4
Order By: Relevance
“…10 Another Brazilian study found that the score on the Memory Complaints Scale correlated with the MMSE and with measures of visual-spatial abilities and orientation. 18 This study investigated both inquired and spontaneous memory complaints. We found that inquired memory complaints (n=78; 85.7%) were more frequent than spontaneous memory complaints (n=13; 14.3%), in line with Burmester et al, 31 who reported that the frequency of spontaneous memory complaints was lower than when actively investigated with a structured questionnaire, in a large survey with 421 individuals.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…10 Another Brazilian study found that the score on the Memory Complaints Scale correlated with the MMSE and with measures of visual-spatial abilities and orientation. 18 This study investigated both inquired and spontaneous memory complaints. We found that inquired memory complaints (n=78; 85.7%) were more frequent than spontaneous memory complaints (n=13; 14.3%), in line with Burmester et al, 31 who reported that the frequency of spontaneous memory complaints was lower than when actively investigated with a structured questionnaire, in a large survey with 421 individuals.…”
Section: Discussionmentioning
confidence: 99%
“…33 To the best of our knowledge, this is one of the first reports of frequency of SCD in a middle-income country. 18 Considering that SCD is associated with increased risk for developing MCI and AD, 14 a clinical follow-up of these individuals is warranted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, because of the large high number of questions and the length of some questions, applying this questionnaire may be time-consuming. • Memory Complaint Scale (MCS 30,40,43,44 ): This scale comprises two sections with seven items each, scoring from 0 to 2 in each item. Its results are scaled as mild (3-6 points), moderate (7-10 points) or severe (11-14 points) memory complaint.…”
Section: • Memorymentioning
confidence: 99%